GOPE: A MVC driven mobile framework using HTML5 for pervasive device container - Lim, Tong Ming *; Lee, Angela Siew Hoong *; Choi, Yeong Terng * (2013)
Mobile devices such as smart phones and tablets have become part of our life these days. Well designed mobile applications for business specific mobile commerce are still very lacking. GOPE is designed to allow group-buy consumers to access to an online group-buy commerce portal with ease, efficiency and flexible functional needs. The GOPE mobile application offers few key features: location selecting option, deals viewing and selecting option, deals sharing, mobile log in, payment on-the -move, and user account management. The proposed mobile framework is designed using Model-View-Controller (MVC) design pattern with ‘hoke’ to enrich the group buy flexible functional requirements. The GOPE MVC ‘hoke’ technique has successfully fulfill the objective of the project. The GOPE prototype has been tested with a select group of testers and it has demonstrated to have achieved goals of the project.